A Survey of factors Related to Tehran, Shahid Beheshti and Iran Universities Students\' educational and career tendencies - A Pourreza; R Khabiri; A Rahimi Foroushani; E Movahed Kor (Tehran University of Medical Sciences, 2013)
Abstract Background: Today there is still a shortage of postgraduates of medicine for multiple reasons. This study aims to determine factors related to Tehran, Shahid Beheshti and Iran Universities students' educational and career tendencies. Materials and Methods: This is a descriptive cross-sectional study. The study population consists of medical students of Tehran, Shahid Beheshti and Iran Universities of Medical Sciences. A sample of 510 individuals was selected using simple random sampling method proportional to the category size.Data were collected using a structured questionnaire of acceptable validity and reliability. Descriptive statistical methods were used for data analysis. Results: Medicine was selected due to its social dignity, motivation to serve the people and interest in medical sciences affect studying medicine as a major .Existence of Medical Universities, improving information and abilities and the need for medical services in different areas affect physician's choice of working location .Simultaneous activity in both private and governmental sectors , disorganized in governmental sectors compared to well organized and well equipped private sector , affect physicians` choice of working sector . Realistic thinking instead of idealism, lack of adequate support from students and differences between the academic environment with student`s interest affect changing the students' educational and career tendency. Conclusion: Actions like regulating the capacity of medical students admission, improving the quality of studies, modification of human resources , better familiarity of students with medicine field while choosing the university field and financial support for young physicians could improve the situation.